2014
DOI: 10.1016/j.polymdegradstab.2014.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Seawater accelerated ageing of poly(3-hydroxybutyrate-co-3-hydroxyvalerate)

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 38 publications
5
52
0
Order By: Relevance
“…Polyhydroxybutyrate (PHB) bioplastic is biodegraded in aerobic and anaerobic engineered processes as well as natural environments; however anaerobic co-digestion of PHB for the express purpose of waste management and renewable energy has not been investigated (Abou-Zeid et al, 2004;Volova et al, 2010;Gómez and Michel, 2013;Deroiné et al, 2014). Budwill et al (1996) reported that PHB is anaerobically biodegradable in various scenarios but suggested that municipal anaerobic sewage sludge digesters were suitable PHB degrading environment to generate biomethane.…”
Section: Introductionmentioning
confidence: 99%
“…Polyhydroxybutyrate (PHB) bioplastic is biodegraded in aerobic and anaerobic engineered processes as well as natural environments; however anaerobic co-digestion of PHB for the express purpose of waste management and renewable energy has not been investigated (Abou-Zeid et al, 2004;Volova et al, 2010;Gómez and Michel, 2013;Deroiné et al, 2014). Budwill et al (1996) reported that PHB is anaerobically biodegradable in various scenarios but suggested that municipal anaerobic sewage sludge digesters were suitable PHB degrading environment to generate biomethane.…”
Section: Introductionmentioning
confidence: 99%
“…for polyester biodegradation. However, an increasing number of studies have shown that most polyester‐based materials with good biodegradability in soil do not degrade or degrade very slowly in oceans; these materials include poly(lactic acid), polyhydroxybutyrate, poly(butylene succinate), and polycaprolactone . Oceans are characterized by high‐salt, high‐pressure, low‐temperature environments containing mobile and diluted nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Lotto et al 2004 evaluated the effect of temperature in the biodegradation of PHB in soil compost at 24 and 46°C. It is well known that the decrease of temperature reduces and can inhibit the bacterial activity decreasing the biodegradation rate, as verified by Deroiné et al (2014). It is well known that the decrease of temperature reduces and can inhibit the bacterial activity decreasing the biodegradation rate, as verified by Deroiné et al (2014).…”
Section: Biodegradation Of Polyhydoxyalkanoatesmentioning
confidence: 83%
“…The biodegradation of PHA has been verified in several environments, including different kinds of soil: garden soil, paddy field soil, farm soil, infertile garden soil, river bank soil (Wang et al 2005b), sea water (Akmal et al 2003;Deroiné et al 2014;Volova et al 2010;Wang et al 2005b); aerobic activated sludge (Akmal et al 2003;Wang et al 2005b); lake water (Akmal et al 2003), river water (Wang et al 2005b), waste landfill model reactors undergo aerobic and anaerobic conditions (Ishigaki et al 2004). Lotto et al 2004 evaluated the effect of temperature in the biodegradation of PHB in soil compost at 24 and 46°C.…”
Section: Biodegradation Of Polyhydoxyalkanoatesmentioning
confidence: 99%